2022
DOI: 10.1037/pst0000442
|View full text |Cite
|
Sign up to set email alerts
|

Therapist emotion and emotional change with clients: Effects on perceived empathy and session quality.

Abstract: Therapists’ emotion and therapist–client emotional congruence are associated with psychotherapy process and outcome. However, their presession emotional states are not consistently accounted for across studies, and the underlying mechanism is unclear. This study introduces the concepts of directional correspondence (DC), where therapists’ and clients’ emotions move in a similar direction from pre to postsession, and absolute agreement (AA), where therapist and client become closer in emotions from pre to posts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(73 reference statements)
0
4
1
Order By: Relevance
“…The crucial importance of the emotions experienced during the session is further supported by a recent study showing that the emotions of the therapists before the session predict neither their empathy with the patient nor the quality of the session (Chui et al , 2022 ). This is particularly important when considering that an empathetic and positive relationship is not only essential for facilitating change but also necessary for the successful execution of psychotherapeutic interventions (Hayes & Vinca, 2017 ; Peluso & Freund, 2018 ).…”
Section: Introductionmentioning
confidence: 91%
“…The crucial importance of the emotions experienced during the session is further supported by a recent study showing that the emotions of the therapists before the session predict neither their empathy with the patient nor the quality of the session (Chui et al , 2022 ). This is particularly important when considering that an empathetic and positive relationship is not only essential for facilitating change but also necessary for the successful execution of psychotherapeutic interventions (Hayes & Vinca, 2017 ; Peluso & Freund, 2018 ).…”
Section: Introductionmentioning
confidence: 91%
“…Therapeutic presence allows clients to engage in a deeper connection with their therapists, promoting the growth of a therapeutic bond (Zhao et al, 2023). A growing body of evidence (e.g., Chui et al, 2022; Hayes & Vinca, 2017) has demonstrated the positive impact of therapeutic presence, as perceived by clients, on the ability to predict empathy, strengthen therapeutic relationships, and enhance therapy session outcomes. Therefore, it is essential to recognize and assess therapeutic presence from the perspective of the client as a significant factor in the therapeutic process.…”
Section: Therapeutic Presence In Online Environmentmentioning
confidence: 99%
“…One aspect of which is the relationship between the therapist's emotion and the psychotherapy process and outcome. For instance, Chui et al (2022) found that clients' perception of therapist empathy was a mediator between the therapist's emotion and the session outcome. Within which, clients' experience of therapist empathy has long been hypothesized to be a key process in psychotherapy contributing to client change and shown to be a moderately strong predictor of therapy outcome (Elliott et al, 2011(Elliott et al, , 2018.…”
mentioning
confidence: 99%
“…Given that the left hemisphere is generally responsible for linguistic functions, the above neurological evidence supports that discourse particles, despite verbal linguistic elements, encode affective/emotional functions. Also, past studies have shown that therapists’ emotions, attitudes, and nonverbal communication are associated with perceived therapist empathy (Chui et al, 2022; L. S. Greenberg, 2008; L.…”
mentioning
confidence: 99%
See 1 more Smart Citation